An exploratory dimensional approach to premenstrual manifestation of obsessive-compulsive disorder symptoms: A multicentre study - Moreira, Luciana; Bins, Helena; Toressan, Ricardo [UNESP]; Ferro, Cláudia; Harttmann, Thiago; Petribú, Kátia; Juruena, Mário Francisco; do Rosário, Maria Conceição; Ferrão, Ygor Arzeno (Elsevier, 2013)
Objective: In women with obsessive-compulsive disorder (OCD), symptom severity appears to fluctuate over the course of the menstrual cycle. The objective of this paper was to compare female OCD patients with and without premenstrual worsening of obsessive-compulsive symptoms (OCS), in terms of the clinical characteristics of OCD. Methods: This was a cross-sectional study involving 455 women with OCD, of whom 226 (49.7%) had experienced premenstrual OCS worsening and 229 (50.3%) had not (PMOCS-worse and PMOCS-same groups, respectively). Data were collected with the original and dimensional versions of the Yale-Brown Obsessive-Compulsive Scale, as well as with the Beck Depression Inventory (BDI) and Beck Anxiety Inventory (BAI). Results: We found significant differences between the PMOCS-same and PMOCS-worse groups, the latter showing a higher frequency of suicidal ideation (P<.001), suicide attempts (P=.027), current use of selective serotonin reuptake inhibitors (P=.022), lifetime use of mood stabilisers (P=.015), and sexual/religious obsessions (P<.001; OR. =1.90), as well as higher scores on the BDI (P<.001) and BAI (P<.001). Conclusion: Underscoring the fact that OCD is a heterogeneous disorder, there appears to be a subgroup of female OCD patients in whom the premenstrual period is associated with a higher frequency of sexual/religious obsessions, depression, anxiety, and suicidality. This might be attributable to hormonal fluctuations. Further studies are warranted in order to investigate this hypothesis by evaluating such patients at different phases of the menstrual cycle, as well as measuring hormonal levels. © 2012 Elsevier Inc.
Keywords: Luteal phase; Obsessive-compulsive symptoms; Premenstrual period; Symptom dimensions; mood stabilizer; serotonin uptake inhibitor; adult; Beck Depression Inventory; clinical feature; cross-sectional study; disease severity; drug use; female; human; major clinical study; obsessive compulsive disorder; premenopause; religion; sexual behavior; suicidal ideation; Yale Brown Obsessive Compulsive Scale; Adult; Antidepressive Agents; Anxiety; Cross-Sectional Studies; Depression; Female; Humans; Middle Aged; Obsessive-Compulsive Disorder; Premenstrual Syndrome; Psychiatric Status Rating Scales; Serotonin Uptake Inhibitors; Severity of Illness Index; Suicide, Attempted